KAJIAN POTENSI ARUS SUNGAI PENGABUAN DI KECAMATAN TUNGKAL ILIR KAB. TANJAB BARAT SEBAGAI PEMBANGKIT ENERGI UNTUK LISTRIK - Myson Myson (Jurnal Ilmiah Universitas Batanghari Jambi, 2015)
The pengabuan River in the Regency Tanjung Jabung Barat is a source of energy that can be harnessed for the life of the local community. Moreover, that particular 1957 city of Kuala Tanjung Jabung District as the capital of the West is currently experiencing a deficit of electrical energy. Whereas the potential energy is very much owned electricity, there are sourced from gas, wind, the Sun and the current of the river. To be able to memanfaatkanya need to have data on the potential of how much kinetic energy that can be raised. For it it is necessary konprehensip in order that the research data obtained later really approaching reality.In this study performed a calculation of potential stream pengabuan to be utilized as a power plant. The main data that is needed is to get the speed of water flow of the river pengabuan and then calculate the flow of discharge.From the implementation of the field conducted as many as 5 times at one point captured, obtained that the speed of the average flow of the river is m/dt 0.31, flow and discharge of 1.1625 m3/dt with a vast field of capture 3, 75m2. Using the formula kinetic energy, then obtained that for broad areas of capture point 3.75 m2 obtained energy of 55.85 joule/dt. It can be inferred that the river flow pengabuan the transverse pieces per square meter of river can evoke the kinetic energy of joule/dt 14.89 or 14.89 Watts.Key word: stream pengabuan Kuala 1957